2010
DOI: 10.1111/j.1445-5994.2010.02217.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Severe hyponatraemia in elderly hospitalized patients: prevalence, aetiology and outcome

Abstract: Severe hyponatraemia in elderly hospitalized medical patients is more frequent in women and of multifactorial aetiology in 50% of cases. It is most commonly caused by SIADH; CSWS is an unlikely cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 28 publications
3
57
3
1
Order By: Relevance
“…Of 1400 elderly ($65 years) patients admitted to an Israeli hospital, 6.2% had such a disorder (4). The increasing prevalence of hyponatremia with age is best illustrated in an analysis of .300,000 samples obtained from .120,000 patients of various ages (5).…”
Section: Question 1 How Common Is Chronic Hyponatremia In the Elderly?mentioning
confidence: 99%
See 1 more Smart Citation
“…Of 1400 elderly ($65 years) patients admitted to an Israeli hospital, 6.2% had such a disorder (4). The increasing prevalence of hyponatremia with age is best illustrated in an analysis of .300,000 samples obtained from .120,000 patients of various ages (5).…”
Section: Question 1 How Common Is Chronic Hyponatremia In the Elderly?mentioning
confidence: 99%
“…Chronic hyponatremia is frequently multifactorial in the elderly (4,8). In one observational study, more than half of the patients with hyponatremia had more than one cause for the condition.…”
Section: Question 1 How Common Is Chronic Hyponatremia In the Elderly?mentioning
confidence: 99%
“…[21] SIADH was found in only 4.2% patients in our study in contrast to nearly half of the patients studied by Clayton et al [6] A study from Israel concluded that cause of hyponatremia in elderly is multifactorial and reported SIADH in nearly 45% of patients. [24] However, Sozio et al challenged the study on the premise that the diagnosis of SIADH is largely dependent on assessment of volume status of the patients and no marker can assess the volume status of the elderly patients reliably. [25] Most of the previous studies have hinted towards higher mortality due to hyponatremia ranging from 33% to 86%.…”
Section: Discussionmentioning
confidence: 99%
“…Common causes of hyponatremia in geriatric hospitalized patients include drugs (thiazide and loop diuretics, proton pump inhibitors, non steroidal anti-inflammatory agents), co-existing morbidities (congestive cardiac failure, chronic kidney disease, chronic liver disease, respiratory infections, volume overload and dehydration etc. [5][6][7][8][9][10] The most important cause of euvolemic hyponatremia in the elderly is Syndrome of Inappropriate Anti-diuretic Hormone (SIADH) often over diagnosed as the elderly are often dehydrated. [11] With the increase in the proportion of the population that is nearing the age of 60 years or above, paucity of data on major health issues in local population plague proper planning and management.…”
Section: Introductionmentioning
confidence: 99%
“…Especially antidepressants, such as selective serotonin reuptake inhibitors (SSRIs), entail a fivefold risk for hospital admission subsequent to hyponatremia (2).…”
Section: Hyponatremia Is a Common Causementioning
confidence: 99%